Adoption of Cloud-Based Accounting Software in Afghanistan Medium-Sized Enterprises - Hasas, Ansarullah; Wahid Samadzai, Abdul (Journal of Advanced Computer Knowledge and Algorithms, 2025)
Cloud-based accounting software adoption has emerged as a critical factor in enhancing financial management and operational efficiency among medium-sized enterprises (MSEs) worldwide. In Afghanistan, where digital transformation is still evolving, understanding the factors influencing cloud accounting adoption is essential for driving sustainable business growth. This study investigates the awareness, motivations, barriers, and adoption patterns of cloud-based accounting software within Afghan MSEs across diverse sectors. Employing a quantitative research design grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Technology–Organization–Environment (TOE) frameworks, data were collected via structured online questionnaires from 50 key decision-makers in five representative companies. Descriptive and inferential statistical analyses were conducted using SPSS to examine adoption drivers and challenges. Findings reveal that while awareness and perceived benefits such as cost-efficiency and real-time access positively influence adoption, significant barriers including security concerns, inadequate infrastructure, and limited technical expertise hinder broader uptake. Sectoral differences further highlight variability in adoption readiness. The study underscores the importance of tailored strategies to enhance infrastructure, provide targeted training, and develop supportive regulatory frameworks to foster cloud accounting adoption in Afghanistan. These insights offer practical recommendations for policymakers and business leaders aiming to accelerate digital financial transformation within the country’s MSE sector. Limitations related to sample size and geographic focus are acknowledged, with suggestions for future research to explore rural contexts and longitudinal adoption trends.